Evaluation of roof truss system under wind load using SAP 2000 - Sharizan , Ramli (2012)
From past record, one of the top ten natural disasters occurred in Malaysia is windstorm. Windstorm has caused many failures to structure especially roof truss. Designer/Engineer tries to avoid the damage by considering the effect of wind to roof truss system. However the understanding of wind behavior to roof truss system is not well defined. Therefore, designer/engineer had try considered the wind load effect to roof truss in gravity direction. Even though the previous study had shown that the wind load are not only act in gravity direction but it also act on uplift direction. Therefore, this study is to evaluate the performance of the roof truss system which neglected the uplift force. The truss system is evaluate with real wind load data. The data are taken from wind tunnel test experiment from Tokyo Polytechnic University. From the result it shows that roof truss is possible to failure due to the real wind load case. The truss system must be considered real wind condition to avoid failure due to wind.